Roles of traditional local food in developing Lenggong Valley as a food tourism destination - Abdul Raji, Mohd Nazri (2020)
Integrating the relationship between food and tourism destination has been an important issue in the current tourism scenario. Many countries and regions around the world have started to recognize their local food as the core or supporting attraction of the destination. Thus, this study aims to understand and explore the role of local food in developing Lenggong Valley, Perak as a food tourism destination through four main research questions: 1) What is the meaning of Lenggong’s local food?; 2) How local food have been used as promotional tools for Lenggong Valley?; 3) What are the challenges in promoting Lenggong’s local food?; and 4) How local food can be used to develop Lenggong Valley as a food tourism destination? A qualitative method using case study approach was conducted to explore Lenggong's local food and tourism resource as the context for data collection. A total of 15 informants were involved in this study comprised of traditional local food experts, local food providers, homestay owner and local authorities. The data were primarily gathered through in-depth, semi-structured interviews and supported with relevant information from focus group discussion, participant observation, document analysis and audio-visual materials. Data were further analyzed using the constant comparative method in establishing codes and categories for the development of the main themes to answer the research questions. The study found that in developing marketing strategies for the food tourism destination, it starts with identifying and classifying the internal resources. Empirical findings show four components of Lenggong's local food. The four components were: 1) practising traditional food culture using natural ingredients, 2) Malay traditional food as main dishes, 3) freshwater fish sources are used as signature dishes and 4) the used of wild edible plants in traditional cooking. The second step was to evaluate the strengths and weaknesses as the efforts and challenges in local food promotion strategy. This step is crucial in developing the core capabilities of a food tourism marketing strategy. The findings of the study indicated that there were five main criteria of local food promotion strategies, namely through 1) organize traditional food festival, 2) document local food as national heritage food, 3) publish traditional recipe books, 4) market local food through commercialization and 5) promote local food through cooking demonstrations. Meanwhile, local stakeholders and authorities faced a few challenges in these promotional efforts such as 1) changing political landscape, 2) local food is underrecognized as a tourist attraction, 3) lack of tourism facilities and 4) issues in the production and preparation of the local food products. The final step, its required suitable marketing strategies for food tourism development based on existing local food resource and tourism strategies. The marketing strategies of food tourism development comprise of four indicators, namely 1) sustain local food as a tourism product, 2) develop food tourism attractions, 3) strengthen local food promotion strategy and 4) improve and enhance tourist facilities. This study contributes an extended use of food tourism concept and research based theory to construct the rural food tourism framework. This valuable information is advantageous to the state government and related agencies in developing marketing strategies for food tourism destination. Further, it can also benefit the local food producers and homestay providers in offering the traditional local food to the tourists that showcase the identity of Lenggong Valley. Nevertheless, this rural food tourism framework also can be applied to other potential food tourism destinations that might need promotion on their foods using traditional local food to enhance destination attraction and competitive advantage.